Promoting Adoption of Recycling by Municipalities in Developing Countries: Increasing or Redistributing Existing Resources? - Vasquez-Perez, O; Davila-Galvez, S (Elsevier B.V., 2021)
It is usually assumed that income differences may affect recycling by shaping consumer demand. However, the recycling supply may depend on different variables such as area, inhabitants, municipal budget, financial regime, among others. All these factors translate into gaps regarding recycling achievements. In this paper, we study the problem of adoption recycling by municipalities from developing countries. In particular, we study the Santiago Metropolitan Area (Chile). Our research is based on qualitative interviews, quantitative data collection and mathematical modelling. We formulate an optimization model to analyse two policy options in municipal solid waste management (MSWM): increase or redistribution of existing resources. The obtained results show, first, that the concerns among key actors about MSWM can be translated into variables that are statistically significant in the quantitative models to predict probability of adopting recycling. Second, the analysed policy options have different impacts. The increase of the average probability for adoption by redistributing one percentage point of MSWM expenses, is similar to one-half percentage point increased in all municipalities. Third, neither redistribution nor overall resource increases would ensure adoption of recycling in the entire metropolitan area. Finally, we discuss the obtained results in light of qualitative interviews. The specific policy alternatives to implement resource increases are a landfill tax and rising council taxes: both seem politically unfeasible to actors from the MSWM sector. Using an innovative mixed-methods approach, we are able to illustrate both the importance of resource redistribution in the supply-side, and the institutional and political complexity of policy implementation. © 2020 Elsevier B.V.